EXPIRY IN DISCIPLINARY PROCEEDINGS - Barja de Quiroga López, Jacobo (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
The effects of expiry; suspension of deadlines;who can suspend the deadline?; coordination between arts. 43.4 and 44; different suspensions.